AdipoRon prevents myostatin‐induced upregulation of fatty acid synthesis and downregulation of insulin activity in a mouse hepatocyte line. Issue 13 (27th June 2019) - Liu, Xin‐Hua; Pan, Jiang Ping; Bauman, William A.; Cardozo, Christopher P.
Abstract: Liver diseases such as non‐alcoholic fatty liver disease (NAFLD) and non‐alcoholic steatohepatitis (NASH) are characterized by excess hepatic accumulation of lipid droplets and triglycerides which are associated with defective insulin action. Myostatin (Mstn) and adiponectin, secreted by muscle cells and adipocytes, respectively, play important roles in regulating insulin signaling and energy metabolism. The mechanisms underlying the actions of Mstn and adiponectin remain largely unknown. Moreover, the interactions between Mstn and adiponectin in regulating gene expression critical for fatty acid metabolism and insulin action in hepatocytes have not been investigated. The effects of Mstn and AdipoRon, a synthetic adiponectin receptor agonist that is orally active, alone or in combination, on hepatic gene expression and function was investigated. While Mstn increased fatty acid (FA) accumulation and desensitized cellular responses to insulin, AdipoRon protected against Mstn‐induced defects in hepatic gene expression and function. In addition, these effects of Mstn were associated with reduced AMPK and PPAR α activities which were reversed by AdipoRon. Finally, AdipoRon was able to prevent Mstn‐induced activation of the Smad2/3 pathway. These data suggest crosstalk between Mstn‐induced Smad2/3 and adiponectin‐induced AMPK/PPAR α pathways, which may play important roles in the regulation of hepatic gene expression critical for FA metabolism and insulin signaling. In addition, the data suggest that AdipoRon, as an adiponectin receptor agonist, may serve a therapeutic role to reduce the hepatic contribution to the disorders of fat metabolism and insulin action. Abstract : These data suggest crosstalk between Mstn‐induced Smad2/3 and adiponectin‐induced AMPK/PPARα pathways, which may play important roles in the regulation of hepatic gene expression critical for FA metabolism and insulin signaling. In addition, the data suggest that AdipoRon, as an adiponectin receptor agonist, may serve a therapeutic role to reduce the hepatic contribution to the disorders of fat metabolism and insulin action.